2018
DOI: 10.3390/nu10030380
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Plasma 25-Hydroxyvitamin D Concentrations among Breast Cancer Survivors in Korea

Abstract: We identified demographic, lifestyle, and clinical factors associated with vitamin D status among breast cancer survivors. The vitamin D prediction model may be a useful surrogate of circulating 25-hydroxvitamin D (25(OH)D) concentrations when this measure was not available. We included a total of 216 Korean breast cancer survivors aged 21–79 years who had been diagnosed with stage I to III primary breast cancer and had breast cancer surgery at least 6 months before enrolment. We used linear and logistic regre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 56 publications
(70 reference statements)
0
3
0
Order By: Relevance
“…However, these risk factors are generally unmodifiable factors. In contrast, our results indicate that insufficient serum 25(OH)D after the 5-year adjuvant endocrine therapy is a significant risk factor for late recurrence, which can be improved through medication and patient lifestyle modification [ 25 ]. We have thus identified a modifiable risk factor for late recurrence among HR-positive breast cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, these risk factors are generally unmodifiable factors. In contrast, our results indicate that insufficient serum 25(OH)D after the 5-year adjuvant endocrine therapy is a significant risk factor for late recurrence, which can be improved through medication and patient lifestyle modification [ 25 ]. We have thus identified a modifiable risk factor for late recurrence among HR-positive breast cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…Recruitment and data collection of socio-demographic and lifestyle factors, health-behaviour, quality of life, dietary intake and clinical characteristics of participants in this study has been reported elsewhere [19][20][21][22][23]. Participants provided information on socio-demographic factors, including age (in years), marital status, and level of education.…”
Section: Sociodemographic Lifestyle and History Of Diseasesmentioning
confidence: 99%
“…In general, calcitriol alters ROS equilibrium in cancer, reduces cancer proliferation, and has a relevant role in apoptosis and autophagy [38][39][40]. It appears that high serum levels are associated with better survival and DFI [41][42][43][44][45]. In 2010, the Institute of Medicine of the US National Academy of Sciences recommended an intake of 600 IU/day of Vit D (15 µg) to maintain adequate serum 25(OH)D for normal bone mineralization.…”
Section: Vitamin Dmentioning
confidence: 99%